DAMPAK TRANSFORMASI TEKNOLOGI DIGITAL DALAM PELAYANAN KESEHATAN DI DINAS KESEHATAN KABUPATEN OGAN KOMERING ULU TAHUN 2024 - Rani Meilinia Darasirta; Aprilia Lestari; Yahnu Wiguno Sanyoto (Jurnal Riset Multidisiplin Edukasi, 2026)
The transformation of digital technology in the public service sector, particularly in health, is an inevitable necessity. This study aims to analyze the impact of digital transformation in health services at the Health Office of Ogan Komering Ulu Regency in 2024, using five dimensions from Royyana's theory: human resources, process, structure, strategy, and technology adoption. This is a descriptive qualitative study, utilizing in-depth interviews, observations, and documentation. The results show improved service efficiency, data transparency, and speed in public health delivery. However, challenges persist such as limited digital literacy, infrastructure gaps, and resistance to change. The study recommends capacity building, organizational restructuring, and adaptive digital strategies.